Distribution of sediments in the Strait between Belakang Padang Island and Sambu Island of Batam City, Kepulauan Riau Province - Dimas Sochi Satya Mendrofa; Rifardi '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in February 2016 in the strait between Belakang Padang Island and Sambu Island of Batam City in Riau Island Archipelago Province. The aim of the student has to understand the environmental deposition of Pulau Belakang Padang waters based on the analysis of surface sediments distribution. Surface sediment samples were taken using Eckman grab from 20 sampling points, to analyze the grain size and sediment composition. In general, the sediment characteristics of the study area is dominated by the fraction from fine to very fine sand. Environmenal deposition can be devided 4 groups. The first group has a weak current and very unstable oceanographic condition, the second group has a mean size that is more rugged and has lower percentage of clay fraction, third group was characterized by stronger current and slightly more stable oceanographic condition and fourth group has oceanographic conditions with the most strong and more stable current system.Keyword: Sediment, Distribution, Belakang Padang, Sambu, Batam